EEG/MEG Error Bounds for a Dynamic Dipole Source with a Realistic Head Model - Muravchik, C.; Bria, O.; Nehorai, A. (Methods of Information in Medicine, 2000)
This work presents the background and derivation of Cramér-Rao bounds on the errors of estimating the parameters (moment and location) of a dynamic current dipole source using data from electro- and magneto-encephalography. A realistic head model, based on knowledge of surfaces separating tissues of different conductivities, is used.
Keywords: Cramér-Rao Bounds; Electro- and Magneto-Encephalography; Nonlinear Discrete Systems; Equivalent Current Dipole